Technological Innovation Capacity: Impact Factors in National Agricultural Research Organisations in Nigeria - Ukaejiofo, Rex Uzonna (Asian Journal of Agriculture and Rural Development, 2013)
This paper looks at the factors that may impact for Technological Innovations in National Agricultural Research institutes in Nigeria. Factors which existing literature show as influencing agricultural technological innovations were identified and selected. These were presented to research personnel in 12 Research institutes who were requested to indicate their importance to technological innovations on a likert scale type instrument. Their responses were analysed using descriptive statistics. The following factors were rated very highly Autonomy on Authority, Technological development level, information sharing with external linkages, level of technological expertise by key research personnel, Incentives and reward system and an enhanced formal and informal linkage system. These findings are discussed and their implications for innovations in agricultural practice in Nigeria were examined. Deriving from these discussions, are actions and measures capable of further enhancing innovation consciousness while improving technological innovativeness in public Agricultural R&D systems in Nigeria and in most developing countries facing same challenges were suggested.